2005
DOI: 10.1143/jjap.44.2311
|View full text |Cite
|
Sign up to set email alerts
|

Cubic-HfN Formation in Hf-Based High-k Gate Dielectrics with N Incorporation and Its Impact on Electrical Properties of Films

Abstract: We examined the effect of the annealing conditions on cubic-HfN (c-HfN) segregation in N-incorporated hafnium aluminate (HfAlON). Low-temperature activation (850 C, 30 min) leads to the inhibition of c-HfN segregation in HfAlON, which occurs at 1000 C for 30 s. This results in a reduced leakage current of the film in the 850 C annealing. k values of HfAlON (k $22) higher than those of hafnium aluminate are confirmed, through the polarization enhancement by Hf-N bonds without a long-range order of c-HfN. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The values are listed in Table II. Calculated increase with increasing x, and the trend is in accordance with experimental results. 4,[6][7][8][9] The values for the a-Al 48 13 Compared with the experimental values at a low x range, 4,6,7,9 calculated degrees of the increase of the from x =0 to x = 0.2 are reasonable, though the calculated for these amorphous models differ even when the models have the same x. Figure 6͑b͒ shows calculated ele and lat against x.…”
Section: B Amorphous Hfomentioning
confidence: 86%
See 1 more Smart Citation
“…The values are listed in Table II. Calculated increase with increasing x, and the trend is in accordance with experimental results. 4,[6][7][8][9] The values for the a-Al 48 13 Compared with the experimental values at a low x range, 4,6,7,9 calculated degrees of the increase of the from x =0 to x = 0.2 are reasonable, though the calculated for these amorphous models differ even when the models have the same x. Figure 6͑b͒ shows calculated ele and lat against x.…”
Section: B Amorphous Hfomentioning
confidence: 86%
“…The more important feature of amorphous high-k materials is that their dielectric and electric properties, thermal stability, and the material/Si-substrate interfacial structure can be changed by controlling their chemical composition and/or by doping of other element atoms ͑e.g., N atoms͒. [4][5][6][7][8][9][10][11][12][13][14][15] Previous experimental studies have shown that the dielectric constants of a-Hf x Al 1−x O y increase from the a-Al 2 O 3 values ͑8-11͒ to the a-HfO 2 values ͑15-25͒ with increasing Hf content ͑x͒, while the crystallization temperature of a-Hf x Al 1−x O y tends to decrease. [4][5][6] The crystallization temperature should be higher than the annealing temperature, typically about 1000°C, during the CMOS fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…This Si-N bond formation could be the reason why Si incorporation suppresses crystallization of HfSiON. Suppose Si atoms are homogeneously distributed in HfSiON, N atoms are also located apart each other as bonded to Si atoms, and this inhibits the segregation of HfN microcrystal, which usually occurs in HfON films [1]. Therefore, we conclude that Si atoms play a very important role in prohibiting crystallization of HfSiON.…”
Section: Resultsmentioning
confidence: 86%
“…The desirable property of HfSiON is attributed to its inclusion of Si atoms, which usually stabilize an amorphous phase of oxides. On the other hand, Koyama et al reported that micro crystals of the metallic HfN are readily segregated in HfON, and that leads to degradations of the insulating property of HfON [1]. Therefore, the Si inclusion is necessary to fabricate a prominent Hf-based high-k gate dielectric.…”
Section: Introductionmentioning
confidence: 99%
“…It is also effective for enhancing the crystallization temperature [111]. This practice even enhances the dielectric constant of the material [120] as in the case of HfSiO, which is beneficial for the realization of smaller EOT gate stack. …”
Section: Hafnium-aluminum-based Gate Dielectricsmentioning
confidence: 99%